Les risques catastrophiques et l’assurance - Moreau, Rémi (Assurances, 1989)
What do the expressions "catastrophe risks" and ''jumbo risks" mean? A dictionary will generally define a catastrophe as "a sudden extraordinary event which results in great misfortune or ruin". In his article, the author considers the following types of catastrophe risks: natural, accidental, criminal and severe liability. In the next issue, he will review world catastrophes affecting both insureds and insurers, including reinsurers.